Design for Optimized Public Safety and Earthquake Disaster Mitigation With IoT - Jae-Kwang Ahn; Tae-Hyun Kim; Hyounhee Koo (IEEE Access, 2024)
The recent advancements in Internet of Things (IoT) technology have played a pivotal role in the development and implementation of an integrated disaster management system aimed at enhancing public safety and refining disaster mitigation strategies through a technologically sophisticated framework. This study explores the application of earthquake early warning systems in conjunction with ShakeMap data, utilizing these tools to swiftly identify regions at the highest risk of seismic damage and thereby optimize emergency response efforts in the most critical areas. The research involves designing and conducting a pilot test to validate the efficacy of an IoT-based service platform, ensuring its alignment with international standards. The pilot test not only encompassed earthquake scenarios and response models but also evaluated the platform’s capability to tailor response functions based on regional intensity measures. The outcomes of this study demonstrate the categorization of response types into “automatic opening/closing,” “response guidance,” and “automation system linkage,” highlighting the potential of IoT devices to react rapidly and effectively in seismic events. This underscores the significant role that IoT technology can play in enhancing public safety measures in the face of seismic disaster.